Is optimism enough? Gay men's beliefs about HIV and their perspectives on risk and pleasure - Prestage, G.; Down, I.; Bradley, J.; McCann, P.; Brown, Graham; Jin, F.; Hurley, M. (2012)
BACKGROUND:: Measures of HIV treatments optimism were developed in response to increased risk behavior among gay men, but were limited in their capacity to help understand gay men's risk behavior. METHODS:: We explored current beliefs about HIV health and transmission and sexual desire and risk behavior in an online survey of 2306 Australian gay men. The survey included free text components. We conducted 40 qualitative interviews to explore how men's beliefs affected decisions about risk behavior. We conducted a principal components factor analysis on the optimism belief items in the survey, and thematic analysis of the qualitative material was used to interrogate the concepts underpinning these beliefs. RESULTS:: We identified two measures of HIV optimism: Health Optimism (a = 0.791) and Transmission Optimism (a = 0.795). In multivariate analysis, unprotected anal intercourse with casual partners was only associated with HIV transmission optimism regardless of HIV serostatus (P < 0.001). Using the qualitative data, we identified 4 themes in how men think about HIV: "concerned," "unconcerned," "fearful," and "irrelevant." Each theme interpellates the 2 optimism measures. CONCLUSION:: HIV optimism remains a useful indicator of gay men's likelihood to take risk, but technical knowledge, experience, desire, and attitudes to risk may all affect how people respond and often in multiple, sometimes contradictory, directions. Men's beliefs about HIV transmission risk in particular may reflect willingness to pursue pleasure over risk, or, alternatively, morbid fear of any risk. Measures of HIV optimism should be complemented by analysis of the complexities of individuals' assessments of both risk and pleasure in specific sexual contexts. © 2012 American Sexually Transmitted Diseases Association All rights reserved.